The global burden of cancer attributable to risk factors, 2010–19 - Tran, Khanh Bao (2022)
Funding: J A Loureiro reports support for the present manuscript from Scientific Employment Stimulus (FCT; CEECINST/00049/2018) as support to their salary and from UIDB/00511/2020 of the LEPABE, funded by national funds through the FCT/MCTES (PIDDAC) as research support.